AN ANTHROPOLOGICAL REVIEW OF ENDOGAMY: A CASE STUDY OF THE MAIPI COMMUNITY IN NORTH LUWU REGENCY - Rustan Darwis (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2026)
Endogamous marriage continues to be practiced by several traditional communities as part of a kinship system that has been transmitted across generations. Despite ongoing social transformation and increasing public awareness of the concerns commonly associated with marriages between relatives, the practice remains prevalent within the Maipi community of North Luwu Regency, Indonesia. Therefore, this study aims to examine the anthropological dimensions of endogamous marriage by exploring the kinship system that sustains the practice, its socio-cultural functions, and the role of family influence in marital decision-making. This study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observation, and document analysis involving customary leaders, community figures, and individuals engaged in endogamous marriages. The findings reveal that endogamous marriage in Maipi is primarily practiced within kinship networks and is maintained as a mechanism for preserving family continuity, strengthening social solidarity, and sustaining the collective identity of the community. Furthermore, family members play a significant role in encouraging marriages among relatives because such unions are believed to foster trust, maintain harmonious relationships between families, and minimize potential social conflicts. Although the community has become increasingly cautious about marriages between close cousins, endogamous marriage continues to enjoy strong social legitimacy as it is perceived to be consistent with local cultural values and religious norms. Thus, endogamous marriage remains an important social institution for maintaining family cohesion and ensuring the continuity of the kinship system within the Maipi community amid ongoing social change.